Modes of Annotation in the Video-Based Corpus FrancoToile: Developing a Design Method. Issue 1 (30th November 2017) - Caws, Catherine; Arneil, Stewart
In corpus linguistics, texts are typically annotated in order to focus the attention on: (a) the form of the text or words, and (b) the structure of sentences (that is, morphological and syntactic tagging). Yet, when dealing with language learning and the development of skills other than just linguistic ones, other types of annotations are needed. Annotating with either a specific learner or pedagogy in mind often engages the researcher in more complex issues than the ones just related to corpus linguistics. In this article, we report on the methods used to create a digital library of videos and annotated transcripts called FrancoToile (http://francotoile.uvic.ca ). As a needs-driven corpus, FrancoToile includes annotations within the video transcripts in order to help users develop their cultural and linguistic literacies in French. These annotations must relate directly to the purpose of the system (the development of cultural and linguistic literacies) and to the specific skill or competency that we hope language learners will gain. We analyze learning needs, modify the software, and observe and engage with users on an ongoing basis to create a language tool that will better address users' needs. This approach of incorporating user feedback increases the usefulness of the annotated videos. We continue to seek means to encourage the involvement of users, both teachers and learners, in the process of corpora editing and content building.